Pendidikan Multikultural Bagian Diversity Manajemen - Jailani Syahputra Siregar; Betti Megawati; Nursalimah; Ruwaidah; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2023)
The term Diversity management is something that needs to be discussed in the world of Islamic education management, because the discussion is closely related to the ability or inability of madrasah heads to create a conducive, safe and controlled atmosphere in Islamic educational institutions (madrasah) in the midst of Diversity / Diversity that naturally exists. Based on several definitions of management mentioned above, it speaks of a sense that is focused on certain parts, therefore, it is also necessary to write a more general definition of management which is a process consisting of a series of activities, such as planning, organising, mobilising and controlling/supervising, which are carried out to determine and achieve predetermined goals through the use of human resources and other resources. In the application of Diversity management is inseparable from the application of multicultural education in Islamic educational institutions (madrasas) so that all madrasa residents, especially madrasa students, respect each other, respect prices, mutual tolerance and so on.